(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Overviews, analyzes, and compares common methods for assessing digital transformation within the pharmaceutical sector. Methods: Established digital transformation assessment methodologies were reviewed and analyzed, including Maturity Model-Based, KPI-Based, International Standards Framework-Based, and Industry Reference Model-Based assessments. Results: Generic digital transformation assessment methods show significant limitations in the pharmaceutical sector, often lacking industry specificity, oversimplifying realities, or failing to capture digital transformation’s dynamic nature. A critical finding, highlighted by the Omnichannel Experience Audit, is the necessity of evaluating the end-user perspective. Elements concerning stakeholder engagement and communication (akin to “marketing policy” focusing on relevance, channel effectiveness, trust) and the quality of ongoing interaction and support (related to “customer care after purchase” including accessibility, personalization, issue resolution) positively impact perceived digital transformation success and user satisfaction. However, these vital user-centric factors are often inadequately measured by traditional, internally focused assessments. Conclusion: No single digital transformation assessment method is universally optimal for the highly regulated pharmaceutical industry. A flexible, multi-faceted, and tailored approach, combining elements from various methodologies, is essential. Critically, integrating the end-user (HCPs/patients) perspective is non-negotiable to ensure digital transformation initiatives provide tangible value, improve experiences, and meet stakeholder needs, moving beyond mere internal optimization or compliance. A user-centric assessment strategy is fundamental for successful and sustainable digital transformation in this sector.